Small- and Medium-Size Enterprise Financing in Eastern Europe - Klapper, Leora F.; Sarria-Allende, Virginia; Sulla, Victor (World Bank, Washington, DC, 2014)
There is currently a large interest in understanding firms' access to finance, particularly in the financing of small- and medium-size enterprises (SMEs). But the financing patterns of SMEs across countries is not well understood. For example, little is known about the relative importance of equity, debt, and inter-firm financing for SMEs across countries. The authors use the Amadeus database, which includes financial information on over 97,000 private and publicly traded firms in 15 Eastern and Central European countries. The Amadeus database allows the authors the opportunity to provide a new analysis of the general financing patterns of private firms across a large sample of Eastern European countries. The summary statistics show that the size of the SME sector (as measured by the percentage of total employment) in Eastern European countries is smaller than in most developed economies. Although the authors find in almost every country in the sample a large number of SMEs as a percentage of total firms, the SMEs in Eastern Europe are generally small and hire few employees. However, SMEs seem to constitute the most dynamic sector of the Eastern European economies, relative to large firms. In general, the SME sector comprises relatively younger, more highly leveraged, and more profitable and faster growing firms. This suggests that a new type of firm is emerging in transition economies that is more market- and profit-oriented. But at the same time, these firms appear to have financial constraints that impede their access to long-term financing and ability to grow.